An address delivered on the consecration of the Worcester Rural Cemetery, September 8, 1838 - Lincoln, Levi (National aegis (Worcester, Mass.), 1838)
Address -- Appendix: Report / William Lincoln -- Lines on the dedication of the Rural Cemetery, first published in the National ægis.